A State of Review on The Current Advances in The Natural Language Processing Technology and Its Applications - Shaik Mohammad Rafi (AG Volumes, 2022)
The field of Artificial Intelligence (AI) that is known as "Natural Language Processing" (NLP) focuses on making computers understand the human language. Using machine learning with NLP algorithms, NLP is able to understand, analyse, and extract meaning from text as well as speech using the power of both linguistics and computer science to study the principles as well as structure of the language. The idea that computers might understand human language was unimaginable just a short time ago. NLP, on the other hand, has grown to be one of AI's most promising and fastest-growing fields in a relatively short period of time, thanks to advances in linguistics, computer science, including machine learning. This paper reviews some of the recent advancements in the NLP technology and its applications in various fields.